The Effectiveness of Using Sondet Smart Augmented Reality Based Application to Improve Sound Understanding for Hearing Impairment Special School Students in Central Java - Nugraheni, Permata Primadhita; Subagya, Subagya (Angstrom Centre of Education, 2024)
Hearing impairment children are individuals who have lost the ability to hear, thereby hampering the process of information through their hearing, whether they use hearing aids or not. This research will test the effectiveness of using the Sondet Smart Augmented Reality based application in improving sound understanding for hearing impairment children. This research uses a quantitative approach with experimental techniques to test the use of the Sondet Smart Augmented Reality based application. The research subjects involved 124 hearing impairment students attending special schools in Central Java, then these students were divided into two groups, control and experimental groups. The research results were calculated using SPSS with the Chi Square test resulting in a asymp-sig calculation of 0.010 using alpha of 0.05, so asymp-sig. < 0.05. Therefore, the use of the sondet application to improve the sound understanding of hearing impairment students in Central Java has proven to be effective in increasing students' sound understanding.